ANALYSIS OF FLAT PLATE COLLECTOR EFFICIENCY IN SOLAR WATER HEATER - Galan Raditya Saputra; Noor Fachrizal (VANOS Journal of Mechanical Engineering Education, 2019)
In Solar Water Heaters require collectors to absorb solar radiation. This absorbed radiation is useful for heating fluid (water) which is used to heat water for domestic use. To get the desired water temperature, the collector must meet certain criteria. In this test, conducted in the Testing Laboratory of Solar Water Heater B2TKE-BPPT for 3 days at 08.30 to 16.00 WIB using a flat plate collector covering an area of 2 m2 with a tank capacity of 150 liters, testing refers to SNI 3021-1992 1st edition. The data taken are Solar Radiation (W/m2), Ambient Temperature (T-amb), Temperature of Inlet Collector (T-in), Water Temperature Out of Collector (T-out) using the help of sensors that have been installed in accordance with the provisions and data generated will be managed via a computer every 30 minutes interval on an ongoing basis. This test, obtained results that the daily average of the efficiency of a flat plate collector of 2 m2 is 46.55%, which means that a solar panel is only able to absorb 46.55% of the solar radiation that illuminates the solar collector. For optimal results, testing should be carried out during clear weather so that collector efficiency can be achieved.